2014
DOI: 10.1007/s10801-014-0554-1
|View full text |Cite
|
Sign up to set email alerts
|

Strongly regular graphs with the $$7$$ 7 -vertex condition

Abstract: The t-vertex condition, for an integer t ≥ 2, was introduced by Hestenes and Higman (SIAM Am Math Soc Proc 4:41-160, 1971) providing a combinatorial invariant defined on edges and non-edges of a graph. Finite rank 3 graphs satisfy the condition for all values of t. Moreover, a long-standing conjecture of Klin asserts the existence of an integer t 0 such that a graph satisfies the t 0 -vertex condition if and only if it is a rank 3 graph. We present the first infinite family of non-rank 3 strongly regular graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…It is well known that a strongly regular graph Γ is (3,4)-regular if and only if its subconstituents Γ i (v) are strongly regular with parameters independent from v ∈ V (Γ) (for a proof see, e.g., [31,Proposition 4]). Thus, Ivanov's graph Γ (4) is (3, 4)-regular.…”
Section: Constructions and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that a strongly regular graph Γ is (3,4)-regular if and only if its subconstituents Γ i (v) are strongly regular with parameters independent from v ∈ V (Γ) (for a proof see, e.g., [31,Proposition 4]). Thus, Ivanov's graph Γ (4) is (3, 4)-regular.…”
Section: Constructions and Resultsmentioning
confidence: 99%
“…2005: Reichard shows that the point graphs of GQ(q, q 2 ) are (2, 7)-regular (cf. [31]). 2007: CP shows that the point graphs of PQ(q − 1, q 2 , q 2 − q) are (2, 6)-regular.…”
Section: Introductionmentioning
confidence: 99%
“…Reichard [31] showed that the collinearity graphs of generalized quadrangles satisfy the 5-vertex condition, and that the collinearity graphs of generalized quadrangles GQ(s, s 2 ) satisfy the 7-vertex condition.…”
Section: Generalized Quadranglesmentioning
confidence: 99%
“…Following Hestenes and Higman [14], a strongly regular graph Γ is said to enjoy the t-vertex condition if, for any graph G on at most t nodes and any two distinguished nodes a, b ∈ V (G) the number of graph homomorphisms from G to Γ mapping a to x and b to y depends only on whether x and y are equal, adjacent, or non-adjacent. A recent investigation on this topic is Reichard's paper [24].…”
Section: The Vector Space Of Scaffolds Of Order Twomentioning
confidence: 99%